1
$\begingroup$

I am looking for the convergence of $$\sum\limits_{n=1}^\infty \frac{\sqrt[n]{n} - 1}{n}$$

I have tried ratio test/ root test and tried to compare with other convergent series but I do not get anywhere. Also, limit comparison of $a_n$ didn't seems to work.

$\endgroup$
4
$\begingroup$

Since $\lim_{x\to 0^+}x\ln x= 0$ we have $\exp(x\ln x) \sim 1+x\ln x$, and hence, $$\frac{n^{1/n} - 1}{n} = \frac1n\left(\exp\left(-\frac1n\ln(\frac1n)\right)-1\right)\sim - \frac1{n^2}\ln(\frac1n) = \frac{\ln n}{n^2}$$ hence the convergence follows by Bertrand criteria or by Cauchy condensation test. or comparison test as follows

$$n^{3/2}\frac{\ln n}{n^2}= \frac{\ln n}{n^{1/2}}\to 0,~~as~~n\to\infty\implies \frac{\ln n}{n^2}\le \frac{C}{n^{3/2}}$$

$\endgroup$
  • $\begingroup$ Very frankly, I didn't know that and I believe there is a "much easier" way to solve it (it's an exam problem). $\endgroup$ – Kartik Sharma Feb 7 '18 at 9:58
  • $\begingroup$ I got it now that you added Cauchy condensation test. Thanks! $\endgroup$ – Kartik Sharma Feb 7 '18 at 10:02
  • $\begingroup$ @KartikSharma what criteria have you done in class there are many other way to solve this $\endgroup$ – Guy Fsone Feb 7 '18 at 13:23
4
$\begingroup$

Use:

$\sqrt[n]{n} \le 1+ \dfrac{2}{\sqrt n}, \in \mathbb {Z^+}, n \ge 1.$

$a_n: = \dfrac{n^{1/n}-1}{n} \le \dfrac{2}{n^{3/2}}.$

Hence sum convergent.

Appended:

For $x \ge 0$, $n\ge 2 :$

$(1+x)^n \ge (n^2/4)x^2.$

(Proof: Use Binomial theorem.)

Set $x =\dfrac{2}{√n},$ then

$(1+x)^n = (1+2/√n)^n \ge$

$ (n^2/4)(4/n)= n.$

Hence: $1+2/√n \ge n^{1/n}$.

$\endgroup$
  • 2
    $\begingroup$ How do you get the first inequality ? $\endgroup$ – Yves Daoust Feb 7 '18 at 10:15
  • 1
    $\begingroup$ Yves. Appended. OK now? Thanks for your comment. $\endgroup$ – Peter Szilas Feb 7 '18 at 10:25
1
$\begingroup$

Note that

$$ \frac{n^{1/n} - 1}{n}\sim \frac{\log n}{n^2}$$

thus the given series converges by compartison with

$$\sum\limits_{n=1}^\infty \frac{1}{n^\frac32}$$

$\endgroup$
1
$\begingroup$

Let

$$t:=\frac{n^{1/n}-1}n$$ so that by the binomial theorem

$$(1+nt)^n=1+n^2t+\frac{n^3(n-1)}2t^2+R(t)=n$$ where $R(t)$ is positive. By solving the quadratic equation for the positive root, we can easily show that

$$t=O(n^{-3/2})$$ and this ensures convergence.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.